Reviving Javanese Script through an Engaging Educational Game: Menghidupkan Kembali Aksara Jawa melalui Game Edukasi yang Menarik - A’amin, Bagas Muzaky; Ratna, Ika (Universitas Muhammadiyah Sidoarjo, 2024)
This study introduces an educational game designed to teach the Javanese script to both children and adults. The game features three difficulty levels and aims to enhance intellect and creativity while keeping players engaged. The development process included system requirements analysis, design, implementation, and testing. Results show the game effectively teaches correct reading and spelling of Javanese characters and is easy to use for all ages. This application combines education and entertainment, making it a valuable tool for cultural learning and intellectual growth. Highlight: The game is designed for all ages, including adults. It features three difficulty levels to enhance intellect and creativity. The development process ensures the game is user-friendly and educational. Keywoard: Javanese script, educational game, intellect enhancement, creativity, cultural learning